Effects of High-Fructose Corn Syrup on Bone Health and Gastrointestinal Microbiota in Growing Male Mice - Han, Xiaoqiang; Feng, Zhiguo; Chen, Yizhang; Zhu, Liying; Li, Xiaoqiong; Wang, Xin; Sun, Haibiao; Li, Jinjun (Frontiers in Nutrition, 2022)
Background: Here, we explored the correlation between gut microbiota and bone health and the effects of high-fructose corn syrup (HFCS) on both. Sixteen 3-week-old male C57BL/6J mice were randomly divided into two groups and given purified water (control group) or 30% HFCS in water (HFCS group) for 16 weeks. The effects of HFCS were assessed via enzyme-linked immunosorbent assays, histopathological assays of colon and bone, and 16s rDNA sequence analysis of gut microbiota. Results: The serum of HFCS group mice had lower levels of bone alkaline phosphatase (BALP), bone Gla protein (BGP), insulin-like growth factor 1 (IGF-1), and testosterone, and higher levels of type I collagen carboxyl-terminal telopeptide (ICTP) and tartrate-resistant acid phosphatase (TRAP) than that of the control group. HFCS caused trabecular bone damage by decreasing trabecular number and thickness and increasing trabecular separation. The HFCS group colons were shorter than the control group colons. The HFCS-fed mice showed mild, localized shedding of epithelial cells in the mucosal layer, focal lymphocytic infiltration of the lamina propria, mild submucosal edema, and loosely arranged connective tissue. The HFCS group displayed lower abundance and altered composition of gut microbiota. The abundance of Defluviitaleaceae UCG-011, Erysipelatoclostridium, Ruminococcaceae UCG-009, Lactobacillus, Blautia, and Parasutterella increased, positively correlating with BALP, BGP, IGF-1, and testosterone levels, and negatively correlating with ICTP and TRAP levels. Conclusions: Our study revealed a potential diet-gut microbiota-bone health axis.